The association between gene polymorphisms in voltage-gated potassium channels Kv2.1 and Kv4.2 and susceptibility to autism spectrum disorder - Liu, Zehui; Yang, Xiaolei; Guo, Peiwen; Wang, Feng; Xia, Wei; Chen, Yuxin; Zou, Mingyang; Sun, Caihong (Frontiers in Psychiatry, 2023)
Background: Autism spectrum disorder (ASD) is a heritable form of neurodevelopmental disorder that arises through synaptic dysfunction. Given the involvement of voltage-gated potassium (Kv) channels in the regulation of synaptic plasticity, we aimed to explore the relationship between the genetic variants in the KCNB1 and KCND2 genes (encoding Kv2.1 and Kv4.2, respectively) and the risk of developing ASD. Methods: A total of 243 patients with ASD and 243 healthy controls were included in the present study. Sixty single nucleotide polymorphisms (35 in KCNB1 and 25 in KCND2) were genotyped using the Sequenom Mass Array. Results: There were no significant differences in the distribution of allele frequencies and genotype frequencies in KCNB1 between cases and controls. However, the differences were significant in the allelic distribution of KCND2 rs1990429 (pBonferroni < 0.005) and rs7793864 (pBonferroni < 0.005) between the two groups. KCND2 rs7800545 (pFDR = 0.045) in the dominant model and rs1990429 (pFDR < 0.001) and rs7793864 (pFDR < 0.001) in the over-dominant model were associated with ASD risk. The G/A genotype of rs1990429 in the over-dominant model and the G/A–G/G genotype of rs7800545 in the dominant model were correlated with lower severity in the Autism Diagnostic Interview-Revised restricted repetitive behavior domain. Conclusions: Our results provide evidence that KCND2 gene polymorphism is strongly associated with ASD susceptibility and the severity of restricted repetitive behavior.